Scalar-induced gravitational waves in a ΛCDM cosmology - Sipp, Marvin; Schäfer, Björn Malte (Physical review, 2023)
We reconsider the gravitational wave spectrum induced by scalar perturbations in spatially flat Friedmann-Lemaître-Robertson-Walker spacetimes, focusing on the matter- and Λ-dominated epochs. During matter domination, subhorizon modes are not free, and a commonly applied approximation for the derivative of the tensor perturbation is flawed. We show analytically that this leads to a significant overestimation of the energy density spectrum. In addition, we demonstrate that gauge-dependent nonoscillating tensor perturbations appear in the presence of a cosmological constant. Complementing the analytical calculations, we compute the according present-day spectrum numerically for a Planck-like ΛCDM cosmology, finding that nonoscillating growing modes appear during the transition between matter and Λ domination in conformal Newtonian gauge.